EARLY DETECTION AND PREVENTION OF CERVICAL CANCER THROUGH EDUCATION - Arlym, Lisa Trina; Kadarwati, Rini; Aprillia, Dita; Nobrihas, Maria M.; Jaziroh, Laeli; Ahdah, Siti; Handayani, Delly; Pujiati, Nurisa (International Journal of Engagement and Empowerment (IJE2), 2025)
Cervical cancer is one of the most common types of cancer in women worldwide. The main cause of cervical cancer is infection with oncogenic types of Human Papilloma Virus (HPV), especially types 16 and 18. Early detection through methods such as Pap smear, IVA (Visual Inspection with Acetic Acid), and HPV DNA testing is very important to identify precancerous lesions before they develop into invasive cancer. Public education about cervical cancer prevention, including HPV vaccination, routine screening, and a healthy lifestyle, is a strategic step to reduce the incidence and mortality due to this disease. This community service program aims to increase public awareness of the importance of early detection and prevention of cervical cancer through a structured educational approach. Thus, it is hoped that a community can be created that is more aware of reproductive health and is able to take preventive measures against cervical cancer. Objective: to increase public understanding and knowledge about early detection of cervical cancer and its prevention. Method: Community service is carried out by providing education to the public about early detection of cervical cancer and its prevention. Results: The activity was carried out on Sunday, February 23, 2025, at PKM Chiba, Japan. Twenty-nine people attended community service activities. Educational activities were carried out from preparation to evaluation. The materials provided included early detection and prevention of cervical cancer. Conclusion: Community service activities went smoothly. This educational activity is expected to be recommended and continued by other health workers so that it can increase mothers' confidence in early detection and prevention of cervical cancer.